Premature Coronary Artery Disease Presenting as STEMI in a Teenager - Morni Modi MS; Paul Ndunda MD; Kalgi Modi MD (Journal of Investigative Medicine High Impact Case Reports)
An 18-year-old teenager with significant atherosclerotic cardiovascular disease (ASCVD) risk factors developed acute chest pain. His electrocardiogram showed inferior ST-segment elevations. Emergent coronary angiogram revealed complete thrombotic occlusion of the right coronary artery. He underwent stenting of the culprit lesion with complete clinical recovery and resolution of his electrocardiographic abnormalities secondary to myocardial infarction.